Experiência de estágio no mercado de insumos do polo de agricultura irrigada RN-CE - Pereira, Luiz Arurélio Freitas (Universidade Federal Rural do Semi-Árido, 2018)
The RN-CE Irrigated Pole is a prominent region in terms of fresh fruit production, which has been consolidating in each harvest due to the specialization of these producers and mainly by a growing world demand for healthier foods due to changes in habits world. Companies located in this region seek to achieve in each crop a better result in quality and productivity and for this they rely on the help of the distributors of inputs and multinationals. Insumos Agrícolas LTDA is one of the companies installed at the pole to provide inputs, disseminate new technologies, products and provide technical advisory services through its team of professional agronomist engineers. In this objective context of this stage was to understand how the activities of this company is developed and how it interacts with the others of the pole, in order to contribute to the professional formation of the student
Relatório
Keywords: Canais de Distribuição de Insumos; Fruticultura; Polo Irrigado RN-CE; Input Distribution Channels; Fruticultura; Polo Irrigated RN-CE; CIENCIAS AGRARIAS::AGRONOMIA